1995
DOI: 10.1097/00005373-199512000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reaming versus Nonreaming in Intramedullary Nailing on Local Infection Rate

Abstract: The question of whether the impairment of the endosteal blood supply, which is induced by nailing with reaming of the medullary cavity, increases the risk of a postoperative infection cannot be conclusively answered by studying existing literature. The aim of this study was to investigate the effect of medullary reaming on the occurrence of local infection based on an infection model in the rabbit tibia (n = 44). An infection rate of 50% was found after unreamed nailing, as opposed to an infection rate of 64% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 19 publications
1
17
0
4
Order By: Relevance
“…In one study, common infecting bacteria were staphylococcus aureus; while in another study, the most common isolated bacteria was Escherichia coli, and coagulasenegative staphylococci in the other. The results of this study is consistent with the fascia and Moretti that isolated Gramnegative and coagulase negative Staphylococcus from open fractures of the lower limb in their studies [11][12][13].…”
Section: Resultssupporting
confidence: 91%
“…In one study, common infecting bacteria were staphylococcus aureus; while in another study, the most common isolated bacteria was Escherichia coli, and coagulasenegative staphylococci in the other. The results of this study is consistent with the fascia and Moretti that isolated Gramnegative and coagulase negative Staphylococcus from open fractures of the lower limb in their studies [11][12][13].…”
Section: Resultssupporting
confidence: 91%
“…As described in previous publications this technique allows the determination of the level of bacterial concentrations at which differences in the infection rates of the compared groups are most evident [1,2,4,5,14,22,23]. This concentration is close to the level of the infection dose of 50%1 (ID50) [30].…”
Section: Experimental Procedures and Statisticsmentioning
confidence: 87%
“…There was a low rate of infection in this series. This may partially be due to the fact that the technique is associated with minimal damage to the blood supply of cortical bone locally [8,11]. Other authors have reported an incidence of infection varying from 2-4% to 11.6% [2,15].…”
Section: Discussionmentioning
confidence: 99%